Functional assays to determine the significance of two common XPC 3'UTR variants found in bladder cancer patients - Bishop D; Hall Janet; Bentley Johanne; Vaslin Laurence; Elliott Faye; Scott Gina B; Qiao Boling; Knowles Margaret A; Kiltie Anne E (BMC, 2011)
Abstract Background XPC is involved in the nucleotide excision repair of DNA damaged by carcinogens known to cause bladder cancer. Individuals homozygous for the variant allele of XPC c.1496C > T (p.Ala499Val) were shown in a large pooled analysis to have an increased bladder cancer risk, and we found two 3'UTR variants, *611T > A and c.*618A > G, to be in strong linkage disequilibrium with c.1496T. Here we determined if these two 3'UTR variants can affect mRNA stability and assessed the impact of all three variants on mRNA and protein expression. Methods In vitro mRNA stability assays were performed and mRNA and protein expression measured both in plasmid-based assays and in lymphocytes and lymphoblastoid cell lines from bladder and breast cancer patients. Results The two 3'UTR variants were associated with reduced protein and mRNA expression in plasmid-based assays, suggesting an effect on mRNA stability and/or transcription/translation. A near-significant reduction in XPC protein expression (p = 0.058) was detected in lymphoblastoid cell lines homozygous for these alleles but no differences in mRNA stability in these lines was found or in mRNA or protein levels in lymphocytes heterozygous for these alleles. Conclusion The two 3'UTR variants may be the variants underlying the association of c.1496C > T and bladder cancer risk acting via a mechanism modulating protein expression.